A rare case of hemobilia caused by acute cholecystitis with an underlying gallbladder aneurysm - Hui Yi Sara Cheo; En Xian Sarah Low; Wee Ming Tay (Gastroenterology & Endoscopy)
We present a case of a patient who presented with upper gastrointestinal bleeding, obstructive jaundice and bacteremia, of which the underlying cause turned out to be hemobilia from acute cholecystitis and a gallbladder aneurysm. The patient made a full recovery after laparoscopic cholecystectomy. Our case highlights the importance of having a high index of suspicion for hemobilia and showcases how hemobilia can be a rare cause of persistent obstructive jaundice.